2003
DOI: 10.1128/aem.69.10.5974-5982.2003
|View full text |Cite
|
Sign up to set email alerts
|

Community Composition and Functioning of Denitrifying Bacteria from Adjacent Meadow and Forest Soils

Abstract: We investigated communities of denitrifying bacteria from adjacent meadow and forest soils. Our objectives were to explore spatial gradients in denitrifier communities from meadow to forest, examine whether community composition was related to ecological properties (such as vegetation type and process rates), and determine phylogenetic relationships among denitrifiers. nosZ, a key gene in the denitrification pathway for nitrous oxide reductase, served as a marker for denitrifying bacteria. Denitrifying enzyme … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
159
2
6

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 238 publications
(177 citation statements)
references
References 44 publications
8
159
2
6
Order By: Relevance
“…narG, nirK, nirS and nosZ were amplified using the primer pairs narG1960f (TAYGTSGGSCARGAR-AA)/narG2650r (TTYTCRTACCABGTBGC; Philippot et al, 2002), F1aCu (ATCATGGTSCTGCCGCG)/ R3Cu (GCCTCGATCAGRTTGTGGTT; Throbäck et al, 2004), cd3aF (GTSAACGTSAAGGARACSG G)/R3cd (GASTTCGGRTGSGTCTTGA; Throbäck et al, 2004) and nosZF (CGCTGTTCITCGACAGYC AG)/nosZR (ATGTGCAKIGCRTGGCAGAA; Rich et al, 2003), respectively. Each primer was preceeded by a 6-bp-long barcode (AGCGTC for unturbated and ATATAC for cryoturbated soil samples) to separate sequences after pyrosequencing.…”
Section: Assessment Of Denitrification In Soil Microcosmsmentioning
confidence: 99%
See 1 more Smart Citation
“…narG, nirK, nirS and nosZ were amplified using the primer pairs narG1960f (TAYGTSGGSCARGAR-AA)/narG2650r (TTYTCRTACCABGTBGC; Philippot et al, 2002), F1aCu (ATCATGGTSCTGCCGCG)/ R3Cu (GCCTCGATCAGRTTGTGGTT; Throbäck et al, 2004), cd3aF (GTSAACGTSAAGGARACSG G)/R3cd (GASTTCGGRTGSGTCTTGA; Throbäck et al, 2004) and nosZF (CGCTGTTCITCGACAGYC AG)/nosZR (ATGTGCAKIGCRTGGCAGAA; Rich et al, 2003), respectively. Each primer was preceeded by a 6-bp-long barcode (AGCGTC for unturbated and ATATAC for cryoturbated soil samples) to separate sequences after pyrosequencing.…”
Section: Assessment Of Denitrification In Soil Microcosmsmentioning
confidence: 99%
“…Organisms hosting both types of nitrite reductase are unknown to date (Heylen et al, 2006). The genes coding for the above-named oxidoreductases are commonly used as structural gene markers for the analysis of nitrate reducer and denitrifier communities (Braker et al, 2000;Philippot et al, 2002;Prieme et al, 2002;Rich et al, 2003;Horn et al, 2006;Enwall et al, 2010;Jones and Hallin, 2010;Palmer et al, 2010;Bru et al, 2011). The main products of denitrification that are released into the atmosphere are N 2 or N 2 O. Denitrifiers might lack nitrate reductases and/or N 2 O reductases, and occupy diverse ecological niches (Tiedje, 1988;Zumft, 1997;Shapleigh, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is difficult to use 16S rRNA gene sequences alone to identify N 2 O reducers. Instead, the gene encoding N 2 O reductase (nosZ) has been used to detect potential N 2 O reducers in various environments (Rich et al, 2003). Although nosZ phylogeny is generally in agreement with 16S rRNA gene phylogeny, horizontal gene transfer may have occurred among closely related microorganisms (Dandie et al, 2007;Jones et al, 2008) and we therefore cannot identify N 2 O reducers on the basis of nosZ sequence information alone.…”
Section: Introductionmentioning
confidence: 96%
“…The activity of reductases and the expression of functional genes involved in denitrification process varies among individual strains (Zumft, 1997), and community composition is thus considered to be able to influence functionality at both community and ecosystem levels (Braker et al, 2010). Nevertheless, some studies have reported correlations between abundance and function as well as between structure and function of denitrifying communities (Bremer et al, 2009;Hallin et al, 2009;Rich et al, 2003) while others not Miller et al, 2008;Wertz et al, 2009). Therefore, it is important to determine the correlations among changes in function, abundance and composition of the denitrifying community in an agricultural soil in response to PAHs stress.…”
Section: Introductionmentioning
confidence: 99%